Protocol for an observational cohort study investigating biomarkers predicting seizure recurrence following a first unprovoked seizure in adults. Issue 12 (5th December 2022) - Adan, Guleed H; de Bézenac, Christophe; Bonnett, Laura; Pridgeon, Michael; Biswas, Shubhabrata; Das, Kumar; Richardson, Mark P; Laiou, Petroula; Keller, Simon S; Marson, Tony
Abstract : Introduction: A first unprovoked seizure is a common presentation, reliably identifying those that will have recurrent seizures is a challenge. This study will be the first to explore the combined utility of serum biomarkers, quantitative electroencephalogram (EEG) and quantitative MRI to predict seizure recurrence. This will inform patient stratification for counselling and the inclusion of high-risk patients in clinical trials of disease-modifying agents in early epilepsy. Methods and analysis: 100 patients with first unprovoked seizure will be recruited from a tertiary neuroscience centre and baseline assessments will include structural MRI, EEG and a blood sample. As part of a nested pilot study, a subset of 40 patients will have advanced MRI sequences performed that are usually reserved for patients with refractory chronic epilepsy. The remaining 60 patients will have standard clinical MRI sequences. Patients will be followed up every 6 months for a 24-month period to assess seizure recurrence. Connectivity and network-based analyses of EEG and MRI data will be carried out and examined in relation to seizure recurrence. Patient outcomes will also be investigated with respect to analysis of high-mobility group box-1 from blood serum samples. Ethics and dissemination: This study was approved by North East—Tyne & Wear South Research Ethics Committee (20/NE/0078) and funded by an Association of British Neurologists and Guarantors of Brain clinical research training fellowship. Findings will be presented at national and international meetings published in peer-reviewed journals. Trial registration number: NIHR Clinical Research Network's (CRN) Central Portfolio Management System (CPMS)—44976.